PENGARUH PENGETAHUAN KEWIRAUSAHAAN DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA SISWA DISMK NEGERI 6 PEKANBARU - Muhammad Ridho Alfa Robby; Caska Caska; Sumarno Sumarno (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the effect of entrepreneurial knowledge and family environment on students' interest in entrepreneurship in SMKN 6 Pekanbaru. The data collection technique was carried out by means of documentation to obtain student entrepreneurial knowledge and using a questionnaire to obtain data about the family environment and interest in entrepreneurship. The population used in this study were students of class XI, amounting to 129 students. This study uses the Slovin formula to determine the number of samples used from the entire population with an overall level of 10%, so the sample taken is at least 57 students. The collected data were then tabulated and analyzed using multiple linear regression with the help of SPSS version 22. The results showed that entrepreneurial knowledge and family environment had a significant effect on student interest in entrepreneurship at SMK Negeri 6 Pekanbaru with the regression equation Y = -22543,608 + 566,336X1 + 0,597 X2 and contributed 41% to the interest in entrepreneurship.Key word : Entrepreneurial Knowledge, Family Environment, Entrepreneurial Interest.